Implementation Of Restorative Justice Based On Local Wisdom: Legal And Cultural Perspectives In Indonesia - Rantau, Palupi; Ajeng Aditya Listyani (Universitas Bengkulu, 2025)
This study discussion the implementation the implementation of restorative justice based on local wisdom in the context of law and culture in Indonesia. In Indonesia's multicultural societies, traditional values such as deliberation, mutual cooperation, and traditional peace have long been part of the conflict resolution mechanism. Restorative justice emerges as an alternative approach that emphasizes the restoration of relationships between Between perpetrators, victims, the cummunities, and aligans with traditional legal practices. Through a normative legal approach, this study analyzes the relationship between the principles of restorative justice and local wisdom as recognized by various laws and regulations, such in 1945 constitution, the Criminal Procedure Code, and regulation of the Police and the Attorney General's Office. This study also reviews local practices such as Mekarabah in Bugis-Makassar, Nyapuh Lawang in Central Java, and customary deliberations in Papua. The results of the study show that the application of customary-based on restorative justice can accelerate conflict resolution, strengthen social legitimacy, and reduce the burden on the formal justice system. However, the challenges remain regarding the integration of customary law into the national legal system and the guarantee of human right protections. Therefore, more integrated regulations and consistent implementation standards are needed to ensure that restorative justice is applied fairly, inclusively, and in line with the principles of the rule of law.